Peningkatan Tata Kelola Administrasi Kerja Sama Daerah sebagai Upaya Sinkronisasi Program Misi Dagang dan Sinergi Lintas Instansi - Regina Yuniar; Achmad Hairudin; Agus Satrya Wibowo; Theresia Octaviani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The East Jawa-Central Kalimantan Trade and Investment Mission 2026 in Palangka Raya served as a strategic momentum to strengthen inter-provincial economic synergy. This study analyzed the role of administrative governance as the key to successful regional cooperation, utilizing participatory observation and qualitative-descriptive document analysis. The event recorded transactions and investment commitments exceeding IDR 2,082 trillion across livestock, agriculture, fisheries, forestry, and processing industries. This achievement was supported by solid legal instruments such as MoUs, cooperation agreements, and meeting minutes as accountability foundations. This activity produced a draft administrative documentation guide to enhance institutional capacity. The findings confirm that sustainable economic achievements can only be realized through structured, orderly, and accountable governance.